Parenting Stress in Mothers of Mentally Retarded, Blind, Deaf and Physically Disabled Children - Mohammad Kazem Atefvahid; Mojtaba Habibi Asgarabad; Ahmad Ashouri; Sayed Hadi Sayed Alitabar (Shahid Beheshti University of Medical Sciences, 2017)
Background and Objective: Parents of children with disabilities are poorer physical and mental health and greater stress experience. This study was conducted to evaluate Parenting stress in mothers of mentally retarded, blind, deaf and physically disabled children. Materials and Methods: This study was causal-comparative. The study population included 310 mothers of exceptional children (mothers of children with mental retardation, blind, deaf and physical-motor disabilities) 7 to 12 years of age enrolled in primary schools in the academic year 90-1389 exceptional Tehran. Multi-stage cluster sampling method was used. The data obtained from questionnaires parenting stress using multivariate analysis of variance (MANOVA) were analyzed. Results: The results showed that parenting stress in mothers of blind with mentally retarded, deaf with mentally retarded, physically with blind and deaf children are significantly different. As well as, there was significant difference between the mean score of blind, physical disorders, mentally retarded and deaf groups in terms of distraction- hyperactivity subscale. Conclusion: Mothers of children with mental retardation, physical disorders, blind and deaf have most parenting stress respectively.